Forgiveness Therapy as A Religious Conflict Resolution of Violence Conflict (Carok) in Pamekasan Madura - Takdir, Mohammad; Mushthafa, M.; Akmaliah, Wahyudi (KARSA Journal of Social and Islamic Culture, 2021)
This research efforts to answer the problem of conflict resolution models were used by Madurese society to resolve carok and why forgiveness can overcome carok conflict. The research tries to understand how the forgiveness stages between the parties involved in the case of carok in Madura? This research used a qualitative method to explore the power of forgiveness in the resolve of carok in Bujur Tengah Village, Batu Marmar, Pamekasan. In collecting data, the researcher used observation, interview, documentation, and triangulation techniques, while the analysis techniques used were data reduction, data presentation, and conclusion drawing. This research shows that the forgiveness model becomes a conflict resolution capable of controlling anger and retaliation to achieve true reconciliation. That is because the forgiveness mechanism has extraordinary power to rebuild the relationship or restore the effects of trauma from the victim's family. The forgiveness mechanism of forgiveness in the case of carok cannot be separated from the role of Kiai to resolve the disputes of land swap overland (village treasury) between two parties. The Kiai carries out many stages to accelerate the achievement of reconciliation; namely restoring security conditions, embracing the families of carok victims, strengthening friendship to prevent counter-conflict, the tabayyun process by presenting conflicting parties, accelerating dialogue, and holding reconciliation studies.